Reducing carbon emissions through improved irrigation and groundwater management: a case study from Iran - Karimi, P.; Qureshi, Asad Sarwar; Bahramloo, R.; Molden, David J. (Elsevier, 2012)
Groundwater irrigation consumes considerable energy as well as water resources across the globe. Using a case study from Iran, this paper explores how enhanced farm water management can help in reducing groundwater exploitation and subsequently limiting energy consumption and the carbon footprint of the groundwater economy. Groundwater use for irrigated agriculture in Iran has increased vastly over the last three decades. We estimate that groundwater pumping consumes 20.5 billion kWh electricity and 2 billion liters of diesel and contributes to 3.6% of the total carbon emission of the country. Thus there is an opportunity to reduce energy use and carbon emissions by pumping less water. However, groundwater use remains important for food security. To identify opportunities for water conservation within agricultural fields, the SWAP model was applied to simulate crop growth and field water balance for three major irrigated crops, i.e. wheat, maize, and sugar beet in the Gamasiab River Basin, one of the highest groundwater using irrigated areas of Iran. The model simulations showed that by adopting improved irrigation schedules and improving farm application efficiencies, water productivity will increase, and irrigation water withdrawals from groundwater can be reduced significantly with no reduction in yields. While these improvements may or may not result in water saving and retarding the ground water decline, depending on the fate of excess application, they will have significant water quality, energy, and carbon implications. Such reduction in irrigation application can result in 40% decline in energy consumption and subsequently carbon emission of groundwater use.